Long-acting aldehyde-removing antibacterial wood floor and preparation process thereof

CN122980790APending Publication Date: 2026-10-27YONGKANG WOODCUTTER IND & TRADE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610973142.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-27

Smart Images

  • Figure CN122980790A_ABST
    Figure CN122980790A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of composite materials, and particularly relates to a long-acting formaldehyde-removing antibacterial wooden door and a preparation process thereof. The antibacterial wooden door comprises a door core layer, a formaldehyde-removing antibacterial layer and a wood grain layer. The two surfaces of the door core layer are bonded with the formaldehyde-removing antibacterial layer. The surfaces of the two formaldehyde-removing antibacterial layers are bonded with the wood grain layer. The surfaces of the two wood grain layers are further bonded with the formaldehyde-removing antibacterial layer. The door core layer, the formaldehyde-removing antibacterial layer and the wood grain layer are bonded and formed through hot pressing. In the present application, the formaldehyde-removing antibacterial layer and the wood grain layer are alternately hot-pressed and bonded on the two surfaces of the door core layer in a full wrapping manner, so that the door core layer and the wood grain layer are fully covered by the formaldehyde-removing antibacterial layer on the inside and the outside, and there is no protective dead angle. In addition, the symmetrical structure is adopted, the hot pressing stress is uniform, the problems of deformation, warping and delamination of the plate are eliminated, the structure of the formed wooden door is stable, and the antibacterial and formaldehyde-removing effect is long-lasting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite material technology, specifically to a long-lasting formaldehyde-removing and antibacterial wooden door and its preparation process. Background Technology

[0002] Wooden doors are a common basic building material in interior decoration, widely used in various interior scenarios such as residences, offices, and commercial spaces. Currently, traditional wooden doors on the market have a simple structure, mostly composed of a core substrate and a surface wood grain decorative layer, possessing only basic functions of partitioning, decoration, and protection, with relatively limited functionality. During interior decoration, wall paints, boards, adhesives, furniture, and other decoration materials continuously release harmful gases such as formaldehyde and benzene. Formaldehyde release can last for 3-15 years, and long-term stagnation indoors can seriously harm the human respiratory and nervous systems, making it one of the main indoor air pollutants. Furthermore, the surface of traditional wooden doors is mostly made of ordinary decorative paper or paint, lacking antibacterial and bacteriostatic functions. When wooden doors are in a humid, enclosed indoor environment for extended periods, mold and bacteria easily grow on the surface and internal layers, leading not only to mold, discoloration, and aging damage, but also to the proliferation of bacteria indoors, affecting indoor environmental hygiene and human health.

[0003] Existing wooden doors with formaldehyde-removing or antibacterial functions mostly only have a functional coating applied to the outermost layer. This coating is prone to wear and peeling, has a short lifespan, and cannot provide long-term protection. Furthermore, only the surface layer is functional; the inner layers and core of the door are unprotected, creating numerous blind spots. The formaldehyde-removing and antibacterial effects are poor and lack persistence. To address the shortcomings of existing technology, there is an urgent need to develop a wooden door with a stable structure, no blind spots, and long-lasting formaldehyde-removing and antibacterial functions to meet the demands of modern environmentally friendly interior decoration. Summary of the Invention

[0004] In view of the problems existing in the prior art, the purpose of this invention is to provide a long-lasting formaldehyde-removing and antibacterial wooden door and its preparation process.

[0005] To achieve the above objectives, the present invention provides the following technical solution: A long-lasting formaldehyde-removing and antibacterial wooden door, comprising a core layer, a formaldehyde-removing and antibacterial layer, and a wood grain layer; both sides of the core layer are bonded with a formaldehyde-removing and antibacterial layer; a wood grain layer is bonded to the surfaces of both formaldehyde-removing and antibacterial layers; a formaldehyde-removing and antibacterial layer is also bonded to the surfaces of both wood grain layers; the core layer, the formaldehyde-removing and antibacterial layer, and the wood grain layer are all bonded together by hot pressing. The core layer of the door is 30-35mm thick and is any one of high-density fiberboard, medium-density fiberboard, solid wood multilayer board, plywood, and blockboard. The wood grain layer has a thickness of 0.2-0.4mm and can be any one of solid wood veneer, natural wood veneer, or engineered wood veneer.

[0006] As a further preferred embodiment of the present invention, the aldehyde-removing and antibacterial layer is prepared by the following method: 1) Add thermoplastic acrylic resin and deionized water into a high-speed dispersion vessel, stir and disperse at 500-700 r / min for 10-20 min at room temperature to obtain resin base liquid, then add dispersant and silane coupling agent to resin base liquid, heat to 40-45℃, disperse at constant temperature for 5-10 min, then slowly add inorganic nano antibacterial powder, stir at high speed at 800-1000 r / min for 20-30 min; 2) Cool to 30-35℃, add mesoporous silica support, stir at 300-350r / min for 15-20min, then add formaldehyde scavenger, ultrasonically disperse at 100-200W for 10-20min, stir at 300-350r / min for 10-20min, then filter through a 200-mesh filter, let stand at room temperature for 15-20min to defoam, and you will get the formaldehyde-removing antibacterial resin liquid; 3) Immerse the base paper material completely in the formaldehyde-removing and antibacterial resin liquid at 30-35℃ for 50-70 seconds. After draining, send it to the pre-curing equipment and pre-cur it at 45-48℃ for 3-5 minutes. Then send it to the segmented drying equipment and dry it at 60-65℃ for 5-10 minutes, then at 80-86℃ for 5-10 minutes, and finally at 100-105℃ for 4-6 minutes. After cutting and dust removal, press it onto the artificial board substrate at 120-140℃ and 0.6-1.5MPa for 25-50 seconds using a hot press to obtain the formaldehyde-removing and antibacterial layer.

[0007] Furthermore, by weight, the composition includes 60-70 parts thermoplastic acrylic resin, 15-30 parts deionized water, 0.5-1.0 parts dispersant, 1-2 parts silane coupling agent, 3-5 parts inorganic nano antibacterial powder, 3-6 parts mesoporous silica support, and 8-15 parts formaldehyde scavenger.

[0008] Furthermore, the silane coupling agent is any one of KH550, KH560, and KH570; The dispersant is any one of sodium polyacrylate dispersant, polyether polyurethane dispersant, and naphthalene sulfonate dispersant. The inorganic nano antibacterial powder is any one of nano silver powder, zirconium phosphate silver-supported powder, nano zinc oxide, nano copper oxide, and nano titanium dioxide. The formaldehyde scavenger is any one of polyol amino-modified formaldehyde scavengers, acylhydrazine scavengers, and amino alcohol composite scavengers; The base paper material is any one of monochrome paper, printed paper, and wear-resistant paper; The artificial board substrate has a thickness of 5-10mm and includes any one of plywood, particleboard, high-density fiberboard, medium-density fiberboard, and blockboard.

[0009] As a further preferred embodiment of the present invention, the mesoporous silica support is prepared by the following method: 1) Add silver nitrate to deionized water, stir thoroughly to dissolve, then add polyvinylpyrrolidone, stir until completely dissolved, then add glucose and copper chloride solution in sequence, stir thoroughly to obtain the growth solution; 2) Add the pretreated mesoporous silica to the growth solution, stir thoroughly and then transfer it to the reaction vessel. After sealing, heat it to 160-170℃ and perform a hydrothermal reaction under intermittent ultrasonic treatment for 20-25 hours. After the reaction is completed, allow it to cool naturally to room temperature. After centrifugation, wash it repeatedly with deionized water and anhydrous ethanol, and then dry it to obtain the mesoporous silica support.

[0010] Furthermore, in the growth solution, the ratio of silver nitrate, deionized water, polyvinylpyrrolidone, glucose, and copper chloride solution is (1.5-3.0) g : (300-500) mL : (5-8) g : (1-2) g : (1-2) mL; The copper chloride solution has a concentration of 4-5 mmol / L; The pretreated mesoporous silica and growth solution have a solid-liquid ratio of 1:(50-80)g / mL; The intermittent ultrasound treatment has a power of 100-150W, with a 5-8 minute break after every 20-30 minutes of operation.

[0011] As a further preferred embodiment of the present invention, the pretreated mesoporous silica is prepared by the following method: 1) Place mesoporous silica in a muffle furnace and heat it to 350-400℃ at a rate of 4-5℃ / min. Calcinate it at a constant temperature for 2-5 hours. After calcination, allow it to cool naturally to room temperature and then disperse it in a mixed solvent to prepare a dispersion with a solid content of 8-10wt%. 2) Add 3-aminopropyltriethoxysilane to the dispersion, stir thoroughly, heat to 70-75℃, reflux and stir at a constant temperature for 3-5 hours, and after the treatment is completed, cool naturally to room temperature. Wash repeatedly by centrifugation with anhydrous ethanol and deionized water, and dry to obtain pretreated mesoporous silica.

[0012] Furthermore, the mesoporous silica has a particle size of 50-100 nm and a pore size of 2-5 nm; The mixed solvent is composed of anhydrous ethanol and deionized water in a volume ratio of (8-9):(1-2); The amount of 3-aminopropyltriethoxysilane added is 6-10% of the mass of mesoporous silica.

[0013] A method for preparing a long-lasting formaldehyde-removing and antibacterial wooden door includes the following steps: The bottom layer is the outer formaldehyde-free and antibacterial layer. Then, the wood grain layer is smoothly attached on top of it. The inner formaldehyde-free and antibacterial layer is attached on top of the wood grain layer. Then, the door core layer is placed in the center. The upper side is symmetrically laid in the order of inner formaldehyde-free and antibacterial layer, wood grain layer, and outer formaldehyde-free and antibacterial layer. After the laying is completed, the edges of each layer are corrected. Then, the door is sent into the hot press equipment and kept at a constant temperature and pressure of 130-150℃ and 10-15MPa for 6-10 minutes. Maintain constant pressure, allow the material to cool naturally, release the pressure and discharge it. Trim the edges of the board, apply glue to the side of the board, attach the wood grain layer, and then hot-press the side of the board to obtain the desired formaldehyde-free and antibacterial wooden door.

[0014] As a further preferred embodiment of the present invention, the amount of adhesive applied is 150-180 g / m³. 2 ; The hot pressing is performed at a temperature of 120-130℃, a pressure of 0.7-1.0MPa, and a time of 10-15min.

[0015] Compared with the prior art, the beneficial effects of the present invention are: In this invention, by performing hydroxyl activation treatment and a two-step modification process involving amino grafting on mesoporous silica, the mesoporous channels can be completely opened, eliminating pore blockage defects and significantly improving porosity utilization and loading rate. Simultaneously, the amino active groups on the pore walls and surface can strongly adsorb metal salt precursor crystals, forming dense and uniform anchoring points. During the hydrothermal reaction, nanowires grow epitaxially along these points, forming a chemically bonded intercalation structure with the silica matrix, improving the adhesion of the nanowires and solving the problems of easy detachment and weak bonding of nanowires. The problem is that pretreated mesoporous silica is used as the matrix material, and silver nitrate is used as the metal salt precursor. The strong adsorption of the densely packed amino active sites on the surface and within the pores of the pretreated mesoporous silica allows metal ions to be uniformly anchored and adsorbed onto the inner walls of the pores and the outer surface of the particles, forming uniformly distributed and consistent-sized nanowire nucleation seed sites. This ensures that the subsequent nanowire growth is uniform, does not agglomerate, and does not detach. Under a hydrothermal high-temperature and high-pressure environment, the precursor seed crystals within the pores preferentially nucleate and grow directionally, along the porous particle channels and surface. Vertical epitaxial growth and in-situ deposition of nanowire structures are achieved. During the hydrothermal reaction, intermittent ultrasonic stimulation creates cavitation and uneven ultrasonic vibration, causing some nanowires to grow crookedly and fail to emerge from the pores. These nanowires then become entangled and cross-linked within the pores, forming a network structure. This results in a mesoporous silica support with a network structure inside the pores and vertically grown nanowires on the outside. The silver nanowires deposited on the surface of this support are one-dimensional structures with a large specific surface area, providing numerous silver ion release sites and a large contact area, resulting in excellent antibacterial effects. When introduced into a formaldehyde-removing antibacterial resin liquid, it acts as a carrier. Under ultrasonic stimulation, formaldehyde scavengers can penetrate into the pores of the carrier. The network structure within the pores effectively confines and inhibits the flow of the formaldehyde scavenger, allowing it to slowly release active groups according to changes in indoor formaldehyde concentration and temperature. This continuously reacts with the formaldehyde that has penetrated the pores, achieving a long-lasting and effective formaldehyde removal effect.

[0016] Meanwhile, a large number of nanowires grow vertically on the surface of the mesoporous silica support carrier. On the one hand, this forms a spatial barrier, preventing the carriers from sticking together and improving their dispersion in the formaldehyde-removing and antibacterial resin liquid, resulting in a more uniform coating after application. On the other hand, when the base paper material is immersed in the formaldehyde-removing and antibacterial resin liquid, the nanowires distributed on the outer surface can not only connect with the fibers in the base paper material, but also penetrate into the micropores on the surface of the base paper material. This forms a dual physical connection of pore embedding and fiber connection, allowing a large number of mesoporous silica support carriers loaded with formaldehyde scavengers to firmly adhere to the base paper material during the impregnation process. This not only helps to increase the amount of formaldehyde scavengers attached to the base paper, but also ensures that the adhesion is firm and not easily lost, so that the formed formaldehyde-removing and antibacterial layer can exert its formaldehyde removal and antibacterial effect.

[0017] In this invention, a fully enclosed method is used to alternately heat-press the formaldehyde-removing and antibacterial layer and the wood grain layer onto both sides of the door core layer. This ensures that both the inner and outer sides of the door core layer and the wood grain layer are fully covered by the formaldehyde-removing and antibacterial layer, leaving no blind spots. Furthermore, the symmetrical structure ensures uniform heat-pressing stress, preventing board deformation, warping, and delamination. The resulting wooden door also has a long-lasting antibacterial and formaldehyde-removing effect. Attached Figure Description

[0018] Figure 1 This is a diagram showing the installation sequence of the long-lasting formaldehyde-removing and antibacterial wooden door in Example 1.

[0019] In the picture: 1. Formaldehyde-removing and antibacterial layer; 2. Wood grain layer; 3. Door core layer. Detailed Implementation

[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] In this embodiment of the invention, the core layer 3 is a high-density fiberboard with a thickness of 35 μm; Wood grain layer 2 is a 0.3mm thick solid wood veneer; The base paper is single-color paper; The silane coupling agent is KH550; The dispersant is sodium polyacrylate dispersant; The inorganic nano-antibacterial powder is nano-silver powder; The formaldehyde scavenger is a polyol amino-modified formaldehyde scavenger; The substrate is a 5mm thick plywood.

[0022] In this embodiment of the invention, the mesoporous silica has a particle size of 80 nm and a pore size of 3 nm.

[0023] Example 1: A long-lasting formaldehyde-removing and antibacterial wooden door, the antibacterial wooden door comprising a core layer 3, a formaldehyde-removing and antibacterial layer 1, and a wood grain layer 2; The preparation method includes the following steps: S1 has the outermost formaldehyde-removing and antibacterial layer 1 laid flat at the bottom, and then the wood grain layer 2 is flatly attached on top of it. The inner formaldehyde-removing and antibacterial layer 1 is attached on top of the wood grain layer 2. S2 places the core layer 3 in the center, and then completes the symmetrical installation on the upper side in the order of inner formaldehyde-removing and antibacterial layer 1, wood grain layer 2, and outer formaldehyde-removing and antibacterial layer 1. After the installation is completed, the edges of each layer are corrected as a whole, and then it is sent into the hot press equipment and kept at a constant temperature and pressure for 6 minutes at 130℃ and 10MPa hot press pressure. S3 maintains constant pressure, allows for natural cooling, then depressurizes and discharges the material. The edges of the boards are trimmed, and then adhesive (formaldehyde-free water-based polyurethane adhesive) is applied to the sides of the boards at a rate of 150g / m². 2 Then, after attaching the wood grain layer 2, hot-press the sides of the board at 120℃ and 0.7MPa for 10 minutes to obtain the desired formaldehyde-free and antibacterial wooden door.

[0024] The preparation method of the formaldehyde-removing antibacterial layer 1 is as follows: 1) Place mesoporous silica in a muffle furnace and heat it to 350°C at a rate of 4°C / min. Calcinate at this temperature for 2 hours. After calcination, allow it to cool naturally to room temperature. Then disperse it in a mixed solvent composed of anhydrous ethanol and deionized water in a volume ratio of 8:2 to prepare a dispersion with a solid content of 8wt%. 2) Add 3-aminopropyltriethoxysilane to the dispersion at 6% of the mass of mesoporous silica. After thorough stirring, heat to 70°C and reflux for 3 hours. After treatment, allow to cool to room temperature naturally. Wash repeatedly with anhydrous ethanol and deionized water by centrifugation, and then vacuum dry at 60°C for 10 hours to obtain pretreated mesoporous silica. 3) Add 1.5g of silver nitrate to 300mL of deionized water, stir thoroughly to dissolve, then add 5g of polyvinylpyrrolidone, stir until completely dissolved, then add 1g of glucose and 1mL of 4mmol / L copper chloride solution, stir thoroughly to obtain the growth solution. 4) Add the pretreated mesoporous silica to the growth solution at a solid-liquid ratio of 1:50 g / mL. After stirring thoroughly, transfer the mixture to a reaction vessel, seal it, and heat it to 160℃. Then, perform a hydrothermal reaction for 20 hours under intermittent ultrasonic treatment at 100W. The ultrasonic treatment is paused for 5 minutes after every 20 minutes of operation. After the reaction is completed, allow it to cool naturally to room temperature. After centrifugation, wash it repeatedly with deionized water and anhydrous ethanol, and dry it to obtain the mesoporous silica support. 5) Add 60 parts of thermoplastic acrylic resin and 15 parts of deionized water into a high-speed dispersion vessel, stir and disperse at 500 r / min for 10 min at room temperature to obtain resin base liquid, then add 0.5 parts of dispersant and 1 part of silane coupling agent to the resin base liquid, heat to 40℃, disperse at constant temperature for 5 min, then slowly add 3 parts of inorganic nano antibacterial powder, and stir at high speed at 800 r / min for 20 min; 6) Cool down to 30℃, add 3 parts of mesoporous silica support, stir at 300r / min for 15min, then add 8 parts of formaldehyde scavenger, ultrasonically disperse at 100W for 10min, stir at 300r / min for 10min, then filter through a 200-mesh filter, let stand at room temperature for 15min to defoam, and you will get the formaldehyde-removing antibacterial resin liquid. 7) Immerse the base paper material completely in the formaldehyde-removing antibacterial resin liquid at 30°C for 50 seconds. After draining, send it to the pre-curing equipment and pre-cur it at 45°C for 3 minutes. Then send it to the segmented drying equipment and dry it at 60°C for 5 minutes, then at 80°C for 5 minutes, and finally at 100°C for 4 minutes. After cutting and dust removal, press it onto the artificial board substrate at 120°C and 0.6MPa for 25 seconds using a hot press to obtain the formaldehyde-removing antibacterial layer 1.

[0025] Example 2: A long-lasting formaldehyde-removing and antibacterial wooden door, the antibacterial wooden door comprising a core layer 3, a formaldehyde-removing and antibacterial layer 1, and a wood grain layer 2; The preparation method includes the following steps: S1 has the outermost formaldehyde-removing and antibacterial layer 1 laid flat at the bottom, and then the wood grain layer 2 is flatly attached on top of it. The inner formaldehyde-removing and antibacterial layer 1 is attached on top of the wood grain layer 2. S2 places the core layer 3 in the center, and then completes the symmetrical installation on the upper side in the order of inner formaldehyde-removing and antibacterial layer 1, wood grain layer 2, and outer formaldehyde-removing and antibacterial layer 1. After the installation is completed, the edges of each layer are corrected as a whole, and then it is sent into the hot press equipment and kept at a constant temperature and pressure for 8 minutes at 140℃ and 12MPa hot press pressure. S3 maintains constant pressure, allows for natural cooling, then depressurizes and discharges the material. The edges of the boards are trimmed, and then adhesive (formaldehyde-free water-based polyurethane adhesive) is applied to the sides of the boards at a rate of 160g / m². 2 Then, after attaching the wood grain layer 2, hot-press the sides of the board at 125℃ and 0.8MPa for 12 minutes to obtain the desired formaldehyde-free and antibacterial wooden door.

[0026] The preparation method of the formaldehyde-removing antibacterial layer 1 is as follows: 1) Place mesoporous silica in a muffle furnace and heat it to 360°C at a rate of 5°C / min. Calcinate at this temperature for 3 hours. After calcination, allow it to cool naturally to room temperature. Then disperse it in a mixed solvent composed of anhydrous ethanol and deionized water in a volume ratio of 9:1 to prepare a dispersion with a solid content of 9wt%. 2) Add 3-aminopropyltriethoxysilane to the dispersion at an amount equal to 8% of the mass of mesoporous silica. After thorough stirring, heat to 72°C and reflux for 4 hours. After treatment, allow to cool naturally to room temperature. Wash repeatedly with anhydrous ethanol and deionized water by centrifugation, and then vacuum dry at 65°C for 12 hours to obtain pretreated mesoporous silica. 3) Add 2.5g of silver nitrate to 400mL of deionized water, stir thoroughly to dissolve, then add 7g of polyvinylpyrrolidone, stir until completely dissolved, then add 1.5g of glucose and 1.5mL of 5mmol / L copper chloride solution, stir thoroughly to obtain the growth solution. 4) Add the pretreated mesoporous silica to the growth solution at a solid-liquid ratio of 1:65 g / mL. After stirring thoroughly, transfer the mixture to a reaction vessel, seal it, and heat it to 165℃. Then, perform a hydrothermal reaction for 23 hours under intermittent ultrasonic treatment at 150W. The ultrasonic treatment is paused for 6 minutes after every 25 minutes of operation. After the reaction is completed, allow it to cool naturally to room temperature. After centrifugation, wash it repeatedly with deionized water and anhydrous ethanol, and dry it to obtain the mesoporous silica support. 5) Add 65 parts of thermoplastic acrylic resin and 25 parts of deionized water into a high-speed dispersion vessel, stir and disperse at 600 r / min for 15 min at room temperature to obtain resin base liquid, then add 0.8 parts of dispersant and 1.5 parts of silane coupling agent to the resin base liquid, heat to 42℃, disperse at constant temperature for 7 min, then slowly add 4 parts of inorganic nano antibacterial powder, and stir at high speed at 900 r / min for 25 min; 6) Cool down to 32℃, add 5 parts of mesoporous silica support, stir at 320r / min for 18min, then add 12 parts of formaldehyde scavenger, ultrasonically disperse at 150W for 15min, stir at 320r / min for 15min, then filter through a 200-mesh filter, let stand at room temperature for 18min to defoam, and you will get the formaldehyde-removing antibacterial resin liquid. 7) The base paper material is completely immersed in the formaldehyde-removing antibacterial resin liquid and impregnated at 32℃ for 60 seconds. After draining, it is sent to the pre-curing equipment and pre-cured at 46℃ for 4 minutes. Then it is sent to the segmented drying equipment and dried at 63℃ for 7 minutes, then at 83℃ for 7 minutes, and finally at 102℃ for 5 minutes. After cutting and dust removal, it is pressed onto the artificial board substrate by a hot press at 130℃ and 1.2MPa for 40 seconds to obtain the formaldehyde-removing antibacterial layer 1.

[0027] Example 3: A long-lasting formaldehyde-removing and antibacterial wooden door, the antibacterial wooden door comprising a core layer 3, a formaldehyde-removing and antibacterial layer 1, and a wood grain layer 2; The preparation method includes the following steps: S1 has the outermost formaldehyde-removing and antibacterial layer 1 laid flat at the bottom, and then the wood grain layer 2 is flatly attached on top of it. The inner formaldehyde-removing and antibacterial layer 1 is attached on top of the wood grain layer 2. S2 places the core layer 3 in the center, and then completes the symmetrical installation on the upper side in the order of inner formaldehyde-removing and antibacterial layer 1, wood grain layer 2, and outer formaldehyde-removing and antibacterial layer 1. After the installation is completed, the edges of each layer are corrected as a whole, and then it is sent into the hot press equipment and kept at a constant temperature and pressure for 10 minutes at 150℃ and 15MPa hot press pressure. S3 maintains constant pressure, allows for natural cooling, then depressurizes and discharges the material. The edges of the boards are trimmed, and then adhesive (formaldehyde-free water-based polyurethane adhesive) is applied to the sides of the boards at a rate of 180g / m². 2 Then, after attaching the wood grain layer 2, hot-press the sides of the board at 130℃ and 1.0MPa for 15 minutes to obtain the desired formaldehyde-free and antibacterial wooden door.

[0028] The preparation method of the formaldehyde-removing antibacterial layer 1 is as follows: 1) Place mesoporous silica in a muffle furnace and heat it to 400℃ at a rate of 5℃ / min. Calcinate it at this temperature for 5 hours. After calcination, allow it to cool naturally to room temperature. Then disperse it in a mixed solvent composed of anhydrous ethanol and deionized water in a volume ratio of 9:1 to prepare a dispersion with a solid content of 10wt%. 2) Add 3-aminopropyltriethoxysilane to the dispersion, the amount of which is 10% of the mass of mesoporous silica. After stirring thoroughly, heat to 75°C and reflux for 5 hours. After the treatment is completed, cool naturally to room temperature, wash repeatedly with anhydrous ethanol and deionized water by centrifugation, and then dry under vacuum at 70°C for 15 hours to obtain pretreated mesoporous silica. 3) Add 3.0g of silver nitrate to 500mL of deionized water, stir thoroughly to dissolve, then add 8g of polyvinylpyrrolidone, stir until completely dissolved, then add 2g of glucose and 2mL of 5mmol / L copper chloride solution, stir thoroughly to obtain the growth solution; 4) Add the pretreated mesoporous silica to the growth solution at a solid-liquid ratio of 1:80 g / mL. After stirring thoroughly, transfer the mixture to a reaction vessel, seal it, and heat it to 170°C. Then, perform a hydrothermal reaction for 25 hours under intermittent ultrasonic treatment at 150 W. The ultrasonic treatment is paused for 8 minutes after every 30 minutes of operation. After the reaction is completed, allow it to cool naturally to room temperature. After centrifugation, wash it repeatedly with deionized water and anhydrous ethanol, and dry it to obtain the mesoporous silica support. 5) Add 70 parts of thermoplastic acrylic resin and 30 parts of deionized water into a high-speed dispersion vessel, stir and disperse at 700 r / min for 20 min at room temperature to obtain resin base liquid, then add 1 part of dispersant and 2 parts of silane coupling agent to the resin base liquid, heat to 45℃, disperse at constant temperature for 10 min, then slowly add 5 parts of inorganic nano antibacterial powder, and stir at high speed at 1000 r / min for 30 min; 6) Cool down to 35℃, add 6 parts of mesoporous silica support, stir at 350r / min for 20min, then add 15 parts of formaldehyde scavenger, ultrasonically disperse at 200W for 20min, stir at 350r / min for 20min, then filter through a 200-mesh filter, let stand at room temperature for 20min to defoam, and you will get the formaldehyde-removing antibacterial resin liquid. 7) The base paper material is completely immersed in the formaldehyde-removing antibacterial resin liquid and impregnated at 35°C for 70 seconds. After draining, it is sent to the pre-curing equipment and pre-cured at 48°C for 5 minutes. Then it is sent to the segmented drying equipment and dried at 65°C for 10 minutes, then at 86°C for 10 minutes, and finally at 105°C for 6 minutes. After cutting and dust removal, it is pressed onto the artificial board substrate by a hot press at 140°C and 1.5MPa for 50 seconds to obtain the formaldehyde-removing antibacterial layer 1.

[0029] Comparative Example 1: This comparative example is the same as Example 1, except that steps 1)-4) are omitted in the preparation of the formaldehyde-removing antibacterial layer 1.

[0030] Comparative Example 2: This comparative example is the same as Example 1, except that steps 1)-2) are omitted in the preparation of the formaldehyde-removing antibacterial layer 1.

[0031] Comparative Example 3: This comparative example is the same as Example 1, except that steps 3)-4) are omitted in the preparation of the aldehyde-removing antibacterial layer 1.

[0032] Comparative Example 4: This comparative example is the same as Example 1, except that the intermittent ultrasonic action in step 4) is omitted in the preparation of the aldehyde-removing antibacterial layer 1.

[0033] Test experiment: Formaldehyde-removing antibacterial layer samples were obtained by processing using the methods disclosed in Examples 1-3 and Comparative Examples 1-4, respectively, and the coating amount of formaldehyde-removing antibacterial resin liquid in each sample was controlled to be 150 g / m². 2 Then, the formaldehyde removal rate was tested in 24 hours according to QB / T2761-2006 "Method for Determining the Purification Effect of Indoor Air Purification Products", and the antibacterial performance was tested according to JIS Z2801:2010. The antibacterial rate was tested, and the results are shown in Table 1.

[0034] Table 1 Performance Test Results As shown in Table 1, the formaldehyde-removing and antibacterial layer prepared by this invention has a high formaldehyde removal rate and a good antibacterial effect. When applied to wooden doors, it enables the wooden doors to maintain their formaldehyde removal and antibacterial effects for many years.

[0035] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A long-lasting formaldehyde-removing and antibacterial wooden door, characterized in that: The antibacterial wooden door includes a core layer, a formaldehyde-removing antibacterial layer, and a wood grain layer; both sides of the core layer are bonded with a formaldehyde-removing antibacterial layer; a wood grain layer is bonded to the surfaces of both formaldehyde-removing antibacterial layers; a formaldehyde-removing antibacterial layer is also bonded to the surfaces of both wood grain layers; the core layer, the formaldehyde-removing antibacterial layer, and the wood grain layer are all bonded together by hot pressing. The core layer of the door is any one of high-density fiberboard, medium-density fiberboard, solid wood multilayer board, plywood, and blockboard. The wood grain layer can be any one of solid wood veneer, natural wood veneer, or engineered wood veneer.

2. The long-lasting formaldehyde-removing and antibacterial wooden door according to claim 1, characterized in that: The specific preparation method of the formaldehyde-removing and antibacterial layer is as follows: 1) Add thermoplastic acrylic resin and deionized water into a high-speed dispersion vessel, stir and disperse at 500-700 r / min for 10-20 min at room temperature to obtain resin base liquid, then add dispersant and silane coupling agent to resin base liquid, heat to 40-45℃, disperse at constant temperature for 5-10 min, then slowly add inorganic nano antibacterial powder, stir at high speed at 800-1000 r / min for 20-30 min; 2) Cool to 30-35℃, add mesoporous silica support, stir at 300-350r / min for 15-20min, then add formaldehyde scavenger, ultrasonically disperse at 100-200W for 10-20min, stir at 300-350r / min for 10-20min, then filter through a 200-mesh filter, let stand at room temperature for 15-20min to defoam, and you will get the formaldehyde-removing antibacterial resin liquid; 3) Immerse the base paper material completely in the formaldehyde-removing and antibacterial resin liquid at 30-35℃ for 50-70 seconds. After draining, send it to the pre-curing equipment and pre-cur it at 45-48℃ for 3-5 minutes. Then send it to the segmented drying equipment and dry it at 60-65℃ for 5-10 minutes, then at 80-86℃ for 5-10 minutes, and finally at 100-105℃ for 4-6 minutes. After cutting and dust removal, press it onto the artificial board substrate at 120-140℃ and 0.6-1.5MPa for 25-50 seconds using a hot press to obtain the formaldehyde-removing and antibacterial layer.

3. The long-lasting formaldehyde-removing and antibacterial wooden door according to claim 2, characterized in that, By weight, the composition includes 60-70 parts thermoplastic acrylic resin, 15-30 parts deionized water, 0.5-1.0 parts dispersant, 1-2 parts silane coupling agent, 3-5 parts inorganic nano antibacterial powder, 3-6 parts mesoporous silica support, and 8-15 parts formaldehyde scavenger.

4. A long-lasting formaldehyde-removing and antibacterial wooden door according to claim 2, characterized in that: The silane coupling agent is any one of KH550, KH560, and KH570; The dispersant is any one of sodium polyacrylate dispersant, polyether polyurethane dispersant, and naphthalene sulfonate dispersant. The inorganic nano antibacterial powder is any one of nano silver powder, zirconium phosphate silver-supported powder, nano zinc oxide, nano copper oxide, and nano titanium dioxide. The formaldehyde scavenger is any one of polyol amino-modified formaldehyde scavengers, acylhydrazine scavengers, and amino alcohol composite scavengers; The base paper material is any one of monochrome paper, printed paper, and wear-resistant paper; The artificial board substrate has a thickness of 5-10mm and includes any one of plywood, particleboard, high-density fiberboard, medium-density fiberboard, and blockboard.

5. A long-lasting formaldehyde-removing and antibacterial wooden door according to claim 2, characterized in that: The mesoporous silica support is prepared by the following method: 1) Add silver nitrate to deionized water, stir thoroughly to dissolve, then add polyvinylpyrrolidone, stir until completely dissolved, then add glucose and copper chloride solution in sequence, stir thoroughly to obtain the growth solution; 2) Add the pretreated mesoporous silica to the growth solution, stir thoroughly and then transfer it to the reaction vessel. After sealing, heat it to 160-170℃ and perform a hydrothermal reaction under intermittent ultrasonic treatment for 20-25 hours. After the reaction is completed, allow it to cool naturally to room temperature. After centrifugation, wash it repeatedly with deionized water and anhydrous ethanol, and then dry it to obtain the mesoporous silica support.

6. A long-lasting formaldehyde-removing and antibacterial wooden door according to claim 5, characterized in that: In the growth solution, the ratio of silver nitrate, deionized water, polyvinylpyrrolidone, glucose, and copper chloride solution is (1.5-3.0) g : (300-500) mL : (5-8) g : (1-2) g : (1-2) mL; The copper chloride solution has a concentration of 4-5 mmol / L; The pretreated mesoporous silica and growth solution have a solid-liquid ratio of 1:(50-80)g / mL; The intermittent ultrasound treatment has a power of 100-150W, with a 5-8 minute break after every 20-30 minutes of operation.

7. A long-lasting formaldehyde-removing and antibacterial wooden door according to claim 5, characterized in that: The pretreated mesoporous silica is prepared by the following method: 1) Place mesoporous silica in a muffle furnace and heat it to 350-400℃ at a rate of 4-5℃ / min. Calcinate it at a constant temperature for 2-5 hours. After calcination, allow it to cool naturally to room temperature and then disperse it in a mixed solvent to prepare a dispersion with a solid content of 8-10wt%. 2) Add 3-aminopropyltriethoxysilane to the dispersion, stir thoroughly, heat to 70-75℃, reflux and stir at a constant temperature for 3-5 hours, and after the treatment is completed, cool naturally to room temperature. Wash repeatedly by centrifugation with anhydrous ethanol and deionized water, and dry to obtain pretreated mesoporous silica.

8. A long-lasting formaldehyde-removing and antibacterial wooden door according to claim 7, characterized in that: The mesoporous silica has a particle size of 50-100 nm and a pore size of 2-5 nm. The mixed solvent is composed of anhydrous ethanol and deionized water in a volume ratio of (8-9):(1-2); The amount of 3-aminopropyltriethoxysilane added is 6-10% of the mass of mesoporous silica.

9. A method for preparing a long-lasting formaldehyde-removing and antibacterial wooden door according to claim 1, characterized in that, Specifically, the steps include the following: The bottom layer is the outer formaldehyde-free and antibacterial layer. Then, the wood grain layer is smoothly attached on top of it. The inner formaldehyde-free and antibacterial layer is attached on top of the wood grain layer. Then, the door core layer is placed in the center. The upper side is symmetrically laid in the order of inner formaldehyde-free and antibacterial layer, wood grain layer, and outer formaldehyde-free and antibacterial layer. After the laying is completed, the edges of each layer are corrected. Then, the door is sent into the hot press equipment and kept at a constant temperature and pressure of 130-150℃ and 10-15MPa for 6-10 minutes. Maintain constant pressure, allow the material to cool naturally, release the pressure and discharge it. Trim the edges of the board, apply glue to the side of the board, attach the wood grain layer, and then hot-press the side of the board to obtain the desired formaldehyde-free and antibacterial wooden door.

10. A method for preparing a long-lasting formaldehyde-removing and antibacterial wooden door according to claim 9, characterized in that: The adhesive application amount is 150-180g / m². 2 ; The hot pressing is performed at a temperature of 120-130℃, a pressure of 0.7-1.0MPa, and a time of 10-15min.